Introducing world Christianity - Farhadian, Charles E. 1964- (Wiley-Blackwell, 2012)
"This is an engaging multidisciplinary introduction to the worldwide spread and impact of Christianity. Bringing together chapters from leading scholars in history, sociology, anthropology, and religious studies, this book examines the major transformations in contemporary societies brought about through the influence of Christianity. Each chapter shows how the broad themes within Christianity have been adopted and adapted by Christian denominations within each major region of the world. So, the book paints a global picture of the impact of Christianity, enriched by detailed historic and ethnographic material for each particular region. Throughout, the chapters examine Protestant, Evangelical, Catholic and Orthodox forms of Christianity. However, the approach is non-theological, focusing on the impact of and response to Christianity, rather than questions of faith. The combination of broader perspectives and deep analysis of particular regions, illuminating the social, cultural, political, and religious features of changes brought about by Christianity, makes this book essential reading for students of world Christianity"-- Provided by publisher